Social support mediates the relationship between illness perception and psychosocial adaptation among young and middle-aged kidney transplant recipients in China - Hu, Na; Wang, Aiping; Chang, Tiantian (Frontiers in Psychology, 2023)
Background No research has yet been done on social support’s influence on the association between illness perception and psychosocial adaptation among young and middle-aged kidney transplant recipients in China. Accordingly, it remains unclear how medical personnel can assist patients in successfully adjusting to the early postoperative period and improving their health. Objective This study sought to explore the influence of illness perception and social support on the psychosocial adaptation of young and middle-aged recipients of kidney transplants in China during the early postoperative period. Methods This study adopted a cross-sectional design. The study included 236 young and middle-aged kidney transplant recipients from a tertiary hospital in China. Demographic and disease-related data were collected. Additionally, the Psychosocial Adjustment to Illness Scale-Self-Report, the Brief Illness Perception Questionnaire, and the Multidimensional Scale of Perceived Social Support were used to assess participants’ psychosocial adaptation, illness perception, and social support, respectively. The model was examined using descriptive analysis, Pearson’s correlation analysis, hierarchical multiple regression analysis, and the PROCESS Macro in SPSS 26.0. Results A total of 176 (74.56%) participants reported an average psychosocial adaptation score >50, which is relatively negative. Marital status, education level, residence, per capita monthly income (in Chinese yuan), medical insurance, work status, post-transplant time, body mass index, creatinine status, and complications were all related to psychosocial adaptation (p < 0.05). The more negative their illness perception and the worse their social support, the worse the psychosocial adaptation of young and middle-aged kidney transplant recipients. Further, the effect of illness perception on psychosocial adaptation was partially mediated by social support (36.56%). Conclusion In general, the psychosocial adaption level of young and middle-aged kidney transplant recipients was negative during the early postoperative period. Healthcare teams should assist patients in building a positive illness perception shortly following kidney transplantation, while also providing psychological care and support to help them cope with the onset of psychosocial issues.